Kaempferia galanga L. Rhizome As a Potential Dental Plaque Preventive Agent - Triana Hertiani; Sylvia Utami Tunjung Pratiwi; Iramie Duma Kencana Irianto; Aini Febriana (Indonesian Journal of Cancer Chemoprevention, 2010)
Dental plaque prevention can be achieved by inhibition of mouth cavity microbes to built biofilm. Kaempferia galanga rhizome has been known as a potential antibacterial agent. This research aimed to reveal the potency of Kaempferia galanga extract and essential oil as anti plaque active agents, based on their in vitro inhibitory activity against the planktonic growth and biofilm of Streptococcus mutans ATCC 21752. Kaempferia galanga extract was obtained by defatting dried-pulverized samples in petroleum ether prior to immersion in 70% ethanol. The fresh rhizome was steam-hydro distilled for 6 h to yield the essential oil. Antibacterial and anti biofilm assays were measured by micro dilution technique on polystyrene 96-wells micro titer plates at 37°C. The percentage of inhibition was calculated by comparing the absorbance of samples to the vehicle (control) measured by micro plate reader at 595 nm. Biofilms formed were first stained by 1% crystal violet. The above assays were performed in triplicates. This study revealed that both K. galanga rhizome essential oil and ethanolic extract showed antibacterial and antibiofilm activity towards S. mutans. The ethanol extract showed MIC90 value at 0.091% w/v and MBC at 2.724% w/v for antibacterial activity; IC50 at 0.048 % w/v for anti biofilm formation activity; and EC50 at 0.052%w/v for biofilm degradation activity. Until the highest concentration tested (0.6%w/v), the MIC90 and MBC values of the essential oil were not revealed, but higher biofilm inhibitory activity i.e. IC50 at 0.025 % w/v; and EC50 at 0.034 %w/v were observed. Key words: biofilm inhibitor, antibacterial, Kaempferia galanga